A kind of high temperature resistant and anti-aging conductive foam

By using materials such as high-temperature resistant ceramic particles and thermoplastic resins in conductive foams, combined with ion implantation and laser-induced surface modification technology, the problems of traditional conductive foams deteriorate performance and poor anti-aging performance in high-temperature environments are solved, and high-strength, high-conductivity and anti-aging conductive foams are achieved, which broadens its application range.

CN119775752APending Publication Date: 2025-04-08SHENZHEN HFC SHIELDING PRODS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411923851.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional conductive foam has deteriorated performance and poor anti-aging properties in high temperature environments, and has complex preparation processes and high cost, which limits its application in extreme environments.

Method used

High-strength, high-conductivity, and anti-aging conductive foams are prepared by using high-temperature resistant ceramic particles, thermoplastic resin polyether ether ketone, metal-organogel and foam metal composite materials.

Benefits of technology

It realizes the excellent conductivity and anti-aging ability of conductive foam in high temperature environments, broadens its application range, and ensures long-term stability and reliability in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775752A_ABST
    Figure CN119775752A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature resistant and anti-aging conductive foam, and relates to the technical field of foam materials. The raw material composition and ingredients are: high-temperature resistant ceramic particles, thermoplastic resin, metal organic gel MOGs and foam metal composite materials, antioxidant-hindered phenol antioxidant and lubricant-zinc stearate. The invention realizes the improvement of the high-temperature resistance and anti-aging performance of the conductive foam through the designed raw material ratio and innovative material combination. Specifically, polyetheretherketone is introduced as a thermoplastic resin matrix, and its good thermal stability and mechanical properties provide strong support for the entire material system. The metal organic gel and the foam metal composite material are integrated into the matrix, which not only enhances the conductive performance of the material, but also enhances the overall stability and durability of the material through its structural characteristics, so that the conductive foam can still maintain excellent performance under high temperature and high pressure, and broadens its application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foam materials, in particular to a high temperature resistant and anti-aging conductive foam. Background Art

[0002] In modern industry and electronics, conductive foam, as an important functional material, is widely used in electromagnetic shielding, anti-static, and sealed conductive fields. With the continuous development of science and technology, the performance requirements for conductive foam are becoming higher and higher, especially in terms of high temperature resistance, aging resistance, and conductivity. Traditional conductive foam materials are often difficult to meet these requirements at the same time, which limits their application in some extreme environments. Therefore, the development of a new type of high temperature resistant and aging resistant conductive foam to meet the urgent needs of the current industrial and electronic fields has become an important research direction.

[0003] Traditional conductive foam preparation technology mainly uses simple physical mixing or chemical cross-linking methods to combine conductive fillers with matrix materials. However, conductive foams prepared by these methods often have many shortcomings. On the one hand, traditional conductive foams are prone to performance degradation in high temperature environments, such as decreased conductivity and weakened mechanical strength, which affects their service life and application effects. On the other hand, traditional conductive foams have poor anti-aging properties. Long-term exposure to harsh environments can easily lead to material aging and cracking, reducing the reliability and stability of the product. In addition, the preparation process of traditional conductive foams is complex and costly, which also limits their large-scale production and wide application.

[0004] Therefore, developing a high temperature resistant and anti-aging conductive foam effectively improves the high temperature resistance and anti-aging properties of the conductive foam while maintaining its good conductive properties, providing a more reliable and efficient conductive material for the development of the modern electronic industry. Summary of the invention

[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and provide a high-temperature resistant and anti-aging conductive foam. Through the designed raw material ratio and innovative preparation process, the excellent conductivity and anti-aging ability of the foam material in a high-temperature environment are achieved. A high-strength and high-conductivity foam matrix is ​​constructed by using thermoplastic resin and metal organic gel and foam metal composite materials, and the surface hardness, wear resistance and electrical properties of the foam are improved through ion implantation and laser-induced surface modification technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a high temperature resistant and anti-aging conductive foam, the raw material composition and ingredients are:

[0007] High temperature resistant ceramic particles: silicon nitride Si3N4: 20-30 parts; boron carbide B4C: 15-25 parts;

[0008] Thermoplastic resin: polyetheretherketone PEEK: 35-50 parts;

[0009] Metal organic gel MOGs and foam metal composite material: 15-30 parts;

[0010] Antioxidant-hindered phenolic antioxidant: 0.5-2 parts;

[0011] Lubricant - zinc stearate: 0.3-1 part.

[0012] Furthermore, in the metal organic gel MOGs and foam metal composite material, the metal organic gel MOGs is self-assembled by metal zinc ions, cobalt ions and organic ligands polycarboxylic acid ligands through coordination bonds, and the weight ratio of the metal organic gel MOGs to the foam metal is 1:2-1:4.

[0013] Furthermore, the preparation process of the conductive foam is as follows:

[0014] S100, surface modification of ceramic particles and mixing with raw materials: surface modification of silicon nitride and boron carbide ceramic particles is performed by using a silane coupling agent solution, and the modified ceramic particles, polyetheretherketone, a composite material of metal organic gel and foamed metal, a hindered phenolic antioxidant, and zinc stearate are mixed in a high-speed mixer, and the polyetheretherketone is stirred at 400-600 r / min for 3-5 minutes, and then the modified ceramic particles, the composite material of metal organic gel and foamed metal, the hindered phenolic antioxidant, and zinc stearate are added and mixed at 800-1200 r / min for 15-30 minutes to obtain a mixed material;

[0015] S200, melt extrusion: add the mixed material into a twin-screw extruder for melting, extrude a uniform melt, the extruder temperature is 320-380°C, and a temperature gradient is set along different areas of the screw, and the screw speed is 30-50r / min;

[0016] S300, extrusion molding and foaming: the melt is extruded through a specific mold and foamed in a foaming device for 3-10 minutes to obtain a foam matrix;

[0017] S400, ion implantation: Place the foam substrate in the sample chamber of the ion implantation equipment and evacuate to 1×10 -3 -1×10 -5 Pa, lanthanum ions were introduced, the accelerating voltage of the ion implantation equipment was adjusted to control the ion beam energy to 30-80 keV, and the ion beam current density was set to control the ion implantation dose to 5×10 15 -2×10 16 ions / cm 2 ;

[0018] S500, laser-induced surface modification: The surface of the foam substrate after ion implantation is scanned by Nd:YAG laser. The foam substrate is placed on the laser processing table. The laser power, scanning speed and spot diameter are controlled by the computer control system. At the same time, a specific microscopic morphology is introduced by the laser.

[0019] S600, preparation and coating of conductive coating: Conductive metal powder and adhesive are weighed in a weight ratio of 7:3, put into a disperser for dispersion and mixing to form conductive coating. The speed of the disperser is set to 1000-1500r / min, and the dispersion time is 20-40 minutes. The conductive coating is evenly coated on the surface of the foam substrate after laser treatment by a coating process;

[0020] S700, drying and curing: dry the coated foam in an oven at a temperature of 80-120°C for 30-60 minutes, transfer the dried foam to a curing oven at a temperature of 130-180°C for 60-150 minutes.

[0021] Furthermore, in the S100, the silane coupling agent in the surface modification of the ceramic particles and the mixing of the raw materials is prepared by dissolving γ-aminopropyltriethoxysilane in an ethanol solution, and the concentration thereof is 2-5wt%.

[0022] Furthermore, in the S100, the surface modification of the ceramic particles is carried out by using a silane coupling agent solution to modify the surface of the silicon nitride and boron carbide ceramic particles during the mixing of the raw materials, the ceramic particles are immersed in the silane coupling agent, the immersion temperature is 60-80°C, the immersion is stirred at a speed of 200-400r / min, the immersion time is 2-4 hours, and after immersion, the particles are filtered and dried, the drying temperature is 80-100°C, and the drying time is 4-6 hours.

[0023] Furthermore, in the extrusion molding and foaming step S300, the foaming agent is azodicarbonamide foaming agent, and the added amount is 1-5% of the total weight of the mixed material.

[0024] Furthermore, in the S300, the foaming temperature during extrusion molding and foaming is 160-220° C., and the pressure is 0.4-0.8 MPa.

[0025] Furthermore, in the S500, the laser power set in the laser induced surface modification is 40-80 W, the scanning speed is 8-15 mm / s, and the spot diameter is 0.5-2 mm.

[0026] Furthermore, in the preparation and coating of the conductive coating in S600, the conductive metal powder is silver powder with an average particle size of 2-8 μm or copper powder with an average particle size of 5-15 μm; and the adhesive is a polyimide adhesive or an epoxy resin adhesive.

[0027] Furthermore, in the S700, the coating process during drying and curing is spraying, the air pressure of the spray gun is 0.3-0.6 MPa, the distance between the spray gun and the surface of the foam substrate is 15-30 cm, and the coating thickness is 0.1-0.2 mm.

[0028] Compared with the prior art, this high temperature resistant and anti-aging conductive foam has the following beneficial effects:

[0029] 1. The present invention achieves the improvement of high temperature resistance and anti-aging performance of conductive foam through the designed raw material ratio and innovative material combination. Specifically, polyetheretherketone is introduced as a thermoplastic resin matrix, and its good thermal stability and mechanical properties provide strong support for the entire material system. The metal organic gel and foam metal composite material are integrated into it, which not only enhances the conductive performance of the material, but also improves the overall stability and durability of the material through its structural characteristics, so that the conductive foam can still maintain excellent performance under high temperature and high pressure, broadening its application range.

[0030] Second, the present invention not only enhances the surface hardness and wear resistance of the foam matrix by controlling the injection process of lanthanum ions, but also effectively improves its surface electrical properties, making its conductive properties more excellent. At the same time, laser-induced surface modification technology is used to introduce a unique micro-morphology on the foam surface through laser scanning processing, further optimizing the surface structure and greatly improving the bonding force between the foam matrix and the conductive coating, which not only comprehensively improves the comprehensive performance of the conductive foam, but also ensures its long-term stability and reliability in extremely harsh environments.

[0031] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 The present invention is a flow chart of the preparation process of a high temperature resistant and anti-aging conductive foam. DETAILED DESCRIPTION

[0034] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0035] Comparative Example 1

[0036] Raw materials are prepared in specific proportions, including 25 parts of silicon nitride (Si3N4), 20 parts of boron carbide (B4C) as high-temperature resistant ceramic particles, 40 parts of polyetheretherketone (PEEK) as thermoplastic resin, 20 parts of metal organic gel MOGs and foam metal composite materials (wherein the metal organic gel MOGs is formed by specific ions and ligands, and the weight ratio with the foam metal is 1:3), 1 part of hindered phenol antioxidant and 0.5 part of zinc stearate as lubricant, in preparation for subsequent preparation.

[0037] The surface modification of ceramic particles is mixed with raw materials. First, γ-aminopropyltriethoxysilane is dissolved in ethanol to prepare a 3wt% concentration of silane coupling agent solution, and then silicon nitride and boron carbide ceramic particles are placed in the solution, immersed at 70°C and 300r / min for 3 hours, then filtered and dried at 90°C for 5 hours for surface modification. Then, the modified ceramic particles and other raw materials are placed in a high-speed mixer, polyetheretherketone is stirred at 500r / min for 4 minutes, and then other ingredients are mixed at 1000r / min for 20 minutes to obtain a mixed material.

[0038] For melt extrusion, add the mixed material into a twin-screw extruder, set the temperature of different zones of the extruder to 320°C in zone 1, 340°C in zone 2, 360°C in zone 3, and 380°C in zone 4 (forming a temperature gradient), and the screw speed to 40r / min, so that the material is melted and extruded to form a uniform melt.

[0039] Extrusion molding and foaming: 3% of azodicarbonamide foaming agent is added to the mixed material, and then the melt is extruded through a specific mold, and foamed in a foaming equipment at 180° C. and 0.6 MPa pressure for 5 minutes to obtain a foam matrix.

[0040] Ion implantation: Place the foam substrate in the sample chamber of the ion implantation equipment and evacuate to 1×10 -4 After 10 Pa, lanthanum ions were introduced, the accelerating voltage was adjusted to make the ion beam energy reach 50 keV, and the current density was set to make the ion implantation dose 1×10 16 ions / cm 2 .

[0041] Laser-induced surface modification: Place the foam substrate on a laser processing workbench and use Nd:YAG laser scanning with a laser power of 60 W, a scanning speed of 10 mm / s, and a spot diameter of 1 mm. At the same time, specific micromorphologies are introduced for surface modification.

[0042] Preparation and coating of conductive coating: copper powder with an average particle size of 5 μm and polyimide adhesive were weighed in a weight ratio of 7:3, put into a high-speed disperser and dispersed and mixed at 1200 r / min for 30 minutes to make a conductive coating, and then coated on the surface of the foam substrate after laser treatment by spraying process, with a spray gun air pressure of 0.4 MPa, 20 cm away from the substrate surface, and a coating thickness of 0.15 mm.

[0043] Drying and curing: the coated foam is first dried in a 100°C oven for 40 minutes, and then transferred to a 150°C curing oven for curing for 100 minutes, and finally a high temperature resistant and anti-aging conductive foam is obtained.

[0044] The high temperature resistant and anti-aging conductive foam prepared by the above steps has an initial decomposition temperature of 500℃ in terms of high temperature resistance. In terms of anti-aging performance, after the foam is placed in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, its tensile strength retention rate is still 85%. The volume resistivity of the foam is 1×10 -3 -1×10 -2 Ω·cm.

[0045] In summary, this comparative example shows in detail the preparation process of high temperature resistant and anti-aging conductive foam. By carefully preparing the raw materials, surface modifying the ceramic particles and mixing them with the raw materials, and then going through a series of steps including melt extrusion, extrusion molding and foaming, ion implantation, laser-induced surface modification, conductive coating preparation and coating, as well as drying and curing, a conductive foam with specific properties is successfully prepared. In each step, the raw material ratio, process parameters and operating conditions are strictly controlled to ensure the effectiveness and stability of each link, so that the final product has excellent performance in high temperature resistance, anti-aging and conductivity, meeting the needs of related fields for high-performance conductive foam materials.

[0046] Embodiment 1

[0047] Raw material preparation: prepare 25 parts of silicon nitride (Si3N4), 20 parts of boron carbide (B4C), 35 parts of polyetheretherketone (PEEK), 20 parts of metal organic gel MOGs and foam metal composite materials (the weight ratio of metal organic gel MOGs to foam metal is 1:3), 1 part of hindered phenol antioxidant, and 0.5 parts of zinc stearate.

[0048] Ceramic particle treatment: Mix with raw materials to prepare silane coupling agent solution (γ-aminopropyltriethoxysilane dissolved in ethanol, 3wt% concentration) for treating ceramic particles (immersion at 70°C, 300r / min for 3 hours, drying at 90°C for 5 hours).

[0049] The modified ceramic particles and other raw materials were put into a high-speed mixer, polyetheretherketone was first stirred at 500 r / min for 4 minutes, and then other ingredients were mixed at 1000 r / min for 20 minutes to obtain a mixed material.

[0050] Melt extrusion: add the mixed material into a twin-screw extruder, set the temperature of different zones of the extruder to 320°C in zone 1, 340°C in zone 2, 360°C in zone 3, and 380°C in zone 4 (forming a temperature gradient), the screw speed to 40r / min, and melt extrude to form a uniform melt.

[0051] Extrusion molding and foaming, adding 3% of azodicarbonamide foaming agent to the mixed material.

[0052] The melt is extruded through a specific die and foamed in a foaming device at 180° C. and a pressure of 0.6 MPa for 5 minutes to obtain a foam matrix.

[0053] Ion implantation: Place the foam matrix in the sample chamber of the ion implantation equipment and evacuate to 1×10 -4 After 10 Pa, lanthanum ions were introduced, the accelerating voltage was adjusted to make the ion beam energy reach 50 keV, and the current density was set to make the ion implantation dose 1×10 16 ions / cm 2 .

[0054] Laser-induced surface modification: Place the foam substrate on a laser processing workbench and use Nd:YAG laser scanning with a laser power of 60W, a scanning speed of 10mm / s, and a spot diameter of 1mm, while introducing a specific microscopic morphology.

[0055] Preparation and coating of conductive coating: copper powder with an average particle size of 5 μm and polyimide adhesive were weighed in a weight ratio of 7:3, put into a high-speed disperser, and dispersed and mixed at 1200 r / min for 30 minutes to prepare the conductive coating.

[0056] The spray coating process was used to coat the surface of the foam substrate after laser treatment, the spray gun air pressure was 0.4MPa, the distance from the substrate surface was 20cm, and the coating thickness was 0.15mm.

[0057] Drying and curing: The coated foam is first dried in a 100°C oven for 40 minutes, and then transferred to a 150°C curing oven for curing for 100 minutes to obtain a high temperature resistant and anti-aging conductive foam.

[0058] The high temperature resistant and anti-aging conductive foam prepared by the above steps has high temperature resistance performance: the initial decomposition temperature is 490℃; anti-aging performance: after aging the foam in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, the tensile strength retention rate is about 82%; conductive performance: tested by the four-probe method, the volume resistivity of the foam is 1×10 -3-5×10 -3 Ω·cm.

[0059] Embodiment 2

[0060] Raw material preparation: 25 parts of silicon nitride, 20 parts of boron carbide, 45 parts of polyetheretherketone, 20 parts of metal organic gel composite material, 1 part of antioxidant, and 0.5 part of zinc stearate.

[0061] The process is the same as that of the first embodiment.

[0062] The high temperature resistant and anti-aging conductive foam prepared by the above steps has high temperature resistance performance: the initial decomposition temperature is 510℃; anti-aging performance: after aging the foam in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, the tensile strength retention rate may be around 88%; conductive performance: tested by the four-probe method, the volume resistivity of the foam is 5×10 -4 -1×10-3Ω·cm.

[0063] Embodiment 3

[0064] Raw material preparation: take 25 parts of silicon nitride, 20 parts of boron carbide, 50 parts of polyetheretherketone, 20 parts of metal organic gel composite material, 1 part of antioxidant, and 0.5 part of zinc stearate.

[0065] The process is the same as that of the first embodiment.

[0066] The high temperature resistant and anti-aging conductive foam prepared by the above steps has high temperature resistance performance: the initial decomposition temperature is 515℃; anti-aging performance: after aging the foam in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, the tensile strength retention rate may be around 90%; conductive performance: tested by the four-probe method, the volume resistivity of the foam is 1×10 -4 -5×10 -4 Ω·cm.

[0067]

[0068] Table 1

[0069] According to Table 1 generated by the above-mentioned Comparative Example 1 and Examples 1 to 3, it can be seen that an appropriate amount of PEEK has many positive effects on the performance of conductive foam. In terms of high temperature resistance, it can significantly improve the stability of the foam in a high temperature environment and broaden the application temperature range; in terms of anti-aging, it helps to maintain the mechanical properties in long-term use and extend the service life; in terms of conductive performance, it can optimize the conductive path and particle dispersion, improve the conductive efficiency, facilitate electromagnetic shielding and electrostatic discharge, and meet the electromagnetic compatibility requirements of electronic equipment. Its own good performance cooperates with other ingredients to improve the overall performance, so that conductive foam is widely used in many fields.

[0070] Embodiment 4

[0071] Raw material preparation: prepare 25 parts of silicon nitride (Si3N4), 20 parts of boron carbide (B4C) as high-temperature resistant ceramic particles, 40 parts of polyetheretherketone (PEEK) as thermoplastic resin, 10 parts of metal organic gel MOGs and foam metal composite materials (wherein the metal organic gel MOGs is formed by specific ions and ligands, and the weight ratio with the foam metal is 1:3), 1 part of hindered phenol antioxidant and 0.5 parts of zinc stearate as lubricant.

[0072] Surface modification of ceramic particles and mixing with raw materials: Preparation of silane coupling agent solution: Dissolve γ-aminopropyltriethoxysilane in ethanol to a concentration of 3 wt %.

[0073] Ceramic particle modification: Place silicon nitride and boron carbide ceramic particles in a silane coupling agent solution, soak at 70°C and 300r / min for 3 hours, filter and dry at 90°C for 5 hours.

[0074] Raw material mixing: put the modified ceramic particles and other raw materials into a high-speed mixer, first stir the polyetheretherketone at 500 r / min for 4 minutes, and then mix the other ingredients at 1000 r / min for 20 minutes to obtain a mixed material.

[0075] Melt extrusion: add the mixed material into a twin-screw extruder, set the temperature of different zones of the extruder to 320°C in zone 1, 340°C in zone 2, 360°C in zone 3, and 380°C in zone 4 (forming a temperature gradient), the screw speed to 40r / min, and melt extrude to form a uniform melt.

[0076] Extrusion molding and foaming: Adding foaming agent: Add 3% of azodicarbonamide foaming agent to the mixed material; Molding and foaming: The melt is extruded through a specific mold, and foamed in a foaming equipment at 180° C. and 0.6 MPa pressure for 5 minutes to obtain a foam matrix.

[0077] Ion implantation: Place the foam substrate in the sample chamber of the ion implantation equipment and evacuate to 1×10 -4 After 10 Pa, lanthanum ions were introduced, the accelerating voltage was adjusted to make the ion beam energy reach 50 keV, and the current density was set to make the ion implantation dose 1×10 16 ions / cm 2 .

[0078] Laser-induced surface modification: Place the foam substrate on a laser processing workbench and use Nd:YAG laser scanning with a laser power of 60W, a scanning speed of 10mm / s, and a spot diameter of 1mm, while introducing a specific microscopic morphology.

[0079] Preparation and coating of conductive coating: Coating preparation: Copper powder with an average particle size of 5 μm and polyimide adhesive are weighed in a weight ratio of 7:3, put into a high-speed disperser and disperse and mix at 1200 r / min for 30 minutes to make a conductive coating; Coating: Spray coating on the surface of the foam substrate after laser treatment, with a spray gun air pressure of 0.4 MPa, 20 cm from the substrate surface, and a coating thickness of 0.15 mm.

[0080] Drying and curing: The coated foam is first dried in a 100°C oven for 40 minutes, and then transferred to a 150°C curing oven for curing for 100 minutes to obtain a high temperature resistant and anti-aging conductive foam.

[0081] The high temperature resistant and anti-aging conductive foam prepared by the above steps has high temperature resistance performance: the initial decomposition temperature is 470℃; anti-aging performance: after aging the foam in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, the tensile strength retention rate may be around 78%; conductive performance: tested by the four-probe method, the volume resistivity of the foam is 1×10 -2 -5×10 -2 Ω·cm.

[0082] Embodiment 5

[0083] Raw material preparation: prepare 25 parts of silicon nitride (Si3N4), 20 parts of boron carbide (B4C), 40 parts of polyetheretherketone (PEEK), 35 parts of metal organic gel MOGs and foam metal composite materials (the weight ratio of metal organic gel MOGs to foam metal is 1:3), 1 part of hindered phenol antioxidant, and 0.5 part of zinc stearate.

[0084] The process is the same as that of the previous embodiment 4.

[0085] The high temperature resistant and anti-aging conductive foam prepared by the above steps has high temperature resistance performance: the initial decomposition temperature is 510℃; anti-aging performance: after aging the foam in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, the tensile strength retention rate may be around 88%; conductive performance: tested by the four-probe method, the volume resistivity of the foam is 5×10 -4 -1×10 -3 Ω·cm.

[0086] Embodiment 6

[0087] Raw material preparation: 25 parts of silicon nitride, 20 parts of boron carbide, 40 parts of polyetheretherketone, 40 parts of metal organic gel composite material, 1 part of antioxidant, and 0.5 part of zinc stearate.

[0088] The process is the same as the previous embodiment 4

[0089] The high temperature resistant and anti-aging conductive foam prepared by the above steps has high temperature resistance: the initial decomposition temperature is 520℃; anti-aging performance: after aging the foam in an aging box at a temperature of 80℃ and a relative humidity of 85% for 1000 hours, the tensile strength retention rate may be around 90%; conductive performance: tested by the four-probe method, the volume resistivity of the foam is 1×10 -4 -5×10 -4 Ω·cm.

[0090]

[0091] Table 2

[0092] According to Table 2 generated by the above-mentioned comparative example 1 and examples 4 to 6, it can be seen that the metal organic gel MOGs and the foam metal composite material have many advantages. Its structural reinforcement effect can enhance the structural integrity of the conductive foam, provide support and prevent decomposition when resistant to high temperature, slow down structural damage and maintain mechanical properties when anti-aging, and help build a stable path when conductive, so that the foam is suitable for complex working conditions; the performance adjustment function allows the content change to balance the high temperature resistance, anti-aging and conductive properties to meet the needs of different application scenarios; the synergistic enhancement characteristics enable the two to interact with each other, not only improving multiple properties, but also having a positive impact on mechanical properties and chemical stability, improving comprehensive performance, broadening the application prospects of conductive foam in the fields of electronics, aerospace, and automobiles, and ensuring its reliable operation in complex working environments. In addition, PEEK itself has good mechanical properties and chemical stability, and can synergize with other components to further improve the comprehensive performance of conductive foam, so that it can be more widely used in multiple fields.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high temperature resistant and anti-aging conductive foam, characterized in that: The raw material composition and ingredients are: High temperature resistant ceramic particles: silicon nitride Si3N4: 20-30 parts; boron carbide B4C: 15-25 parts; Thermoplastic resin: polyetheretherketone PEEK: 35-50 parts; Metal organic gel MOGs and foam metal composite material: 15-30 parts; Antioxidant-hindered phenolic antioxidant: 0.5-2 parts; Lubricant - zinc stearate: 0.3-1 part.

2. The high temperature resistant and anti-aging conductive foam according to claim 1, characterized in that: The metal organic gel MOGs in the metal organic gel MOGs and foam metal composite material is self-assembled by metal zinc ions, cobalt ions and organic ligands polycarboxylic acid ligands through coordination bonds, and the weight ratio of the metal organic gel MOGs to the foam metal is 1:2-1:

4.

3. The high temperature resistant and anti-aging conductive foam according to claim 1, characterized in that: The preparation process of the conductive foam is as follows: S100, surface modification of ceramic particles and mixing with raw materials: surface modification of silicon nitride and boron carbide ceramic particles is performed by using a silane coupling agent solution, and the modified ceramic particles, polyetheretherketone, a composite material of metal organic gel and foamed metal, a hindered phenolic antioxidant, and zinc stearate are mixed in a high-speed mixer, and the polyetheretherketone is stirred at 400-600 r / min for 3-5 minutes, and then the modified ceramic particles, the composite material of metal organic gel and foamed metal, the hindered phenolic antioxidant, and zinc stearate are added and mixed at 800-1200 r / min for 15-30 minutes to obtain a mixed material; S200, melt extrusion: add the mixed material into a twin-screw extruder for melting, extrude a uniform melt, the extruder temperature is 320-380°C, and a temperature gradient is set along different areas of the screw, and the screw speed is 30-50r / min; S300, extrusion molding and foaming: the melt is extruded through a specific mold and foamed in a foaming device for 3-10 minutes to obtain a foam matrix; S400, ion implantation: Place the foam substrate in the sample chamber of the ion implantation equipment and evacuate to 1×10 -3 -1×10 -5 Pa, lanthanum ions were introduced, the accelerating voltage of the ion implantation equipment was adjusted to control the ion beam energy to 30-80 keV, and the ion beam current density was set to control the ion implantation dose to 5×10 15 -2×10 16 ions / cm 2 ; S500, laser-induced surface modification: The surface of the foam substrate after ion implantation is scanned by Nd:YAG laser. The foam substrate is placed on the laser processing table. The laser power, scanning speed and spot diameter are controlled by the computer control system. At the same time, a specific microscopic morphology is introduced by the laser. S600, preparation and coating of conductive coating: Conductive metal powder and adhesive are weighed in a weight ratio of 7:3, put into a disperser for dispersion and mixing to form conductive coating. The speed of the disperser is set to 1000-1500r / min, and the dispersion time is 20-40 minutes. The conductive coating is evenly coated on the surface of the foam substrate after laser treatment by a coating process; S700, drying and curing: dry the coated foam in an oven at a temperature of 80-120°C for 30-60 minutes, transfer the dried foam to a curing oven at a temperature of 130-180°C for 60-150 minutes.

4. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: The silane coupling agent in the S100 ceramic particle surface modification and raw material mixing is prepared by dissolving γ-aminopropyltriethoxysilane in an ethanol solution, and the concentration thereof is 2-5wt%.

5. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: In the S100, surface modification of ceramic particles and raw material mixing is performed on the surface of silicon nitride and boron carbide ceramic particles by using a silane coupling agent solution, the ceramic particles are immersed in the silane coupling agent at a immersion temperature of 60-80° C., stirred at a speed of 200-400 r / min during immersion, and the immersion time is 2-4 hours. After immersion, the particles are filtered and dried at a drying temperature of 80-100° C. and a drying time of 4-6 hours.

6. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: In the S300, the foaming agent in the extrusion molding and foaming is azodicarbonamide foaming agent, and the added amount is 1-5% of the total weight of the mixed material.

7. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: In the S300, the foaming temperature during extrusion molding and foaming is 160-220° C. and the pressure is 0.4-0.8 MPa.

8. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: In the S500, the laser power set in the laser induced surface modification is 40-80 W, the scanning speed is 8-15 mm / s, and the spot diameter is 0.5-2 mm.

9. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: In the above S600, the conductive metal powder in the preparation and coating of the conductive coating is silver powder with an average particle size of 2-8 μm or copper powder with an average particle size of 5-15 μm; and the adhesive is a polyimide adhesive or an epoxy resin adhesive.

10. The high temperature resistant and anti-aging conductive foam according to claim 3, characterized in that: In the S700, the coating process during drying and curing is spraying, the air pressure of the spray gun is 0.3-0.6 MPa, the distance between the spray gun and the surface of the foam substrate is 15-30 cm, and the coating thickness is 0.1-0.2 mm.

Citation Information

Cited By

  • Laser-induced surface metallization glass fiber reinforced polyether-ether-ketone modified material and preparation method thereof

    CN120924003A